Mathematics Learning Planning in the Independence Curriculum - Hakiki, Lintang Sunny; Murtiyasa, Budi; Djumadi, Djumadi (CV. Rayyan Dwi Bharata, 2023)
Mathematics is a very important subject at every level of education in every country. This is proven by making mathematics a basic competency in PISA (program for international student assessment). Based on the results of the 2019 PISA, the ability of Indonesian students to score below the OECD average in reading, mathematics and science. It can be concluded that the reading and mathematics abilities of students in Indonesia still need to be improved, so it is necessary to strengthen literacy and numeracy through effective mathematics learning plans. The purpose of the research is to explain the planning of learning mathematics in the independent curriculum. This research is a qualitative research with a case study. Data collection techniques using observation, interviews and documentation. Data validation uses technique triangulation and source triangulation. Data analysis used interactive data analysis from Miles Huberman. The results showed that the planning of learning mathematics begins with the analysis of learning outcomes, determining learning objectives, determining the flow of learning objectives and making teaching modules.